1982
DOI: 10.1177/036354658201000512
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy in ankle sprains

Abstract: This study assesses recovery from ankle sprains. Thirty-seven final participants were categorized according to the severity of their injury and the use of cryotherapy (15 minutes, one to three times per day) versus heat therapy (15 minutes, one to three times per day) for a minimum of three days. Therapy commenced either less than one hour, from one to 36 hours, or greater than 36 hours after traumatic event. Sprains were graded into five categories based on severity of the injury, but only two categories, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
8

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(72 citation statements)
references
References 8 publications
2
61
1
8
Order By: Relevance
“…Previous research [1][2][3][4][5][6] has shown that decreasing tissue temperature decreases pain, edema, nerve conduction, cellular metabolism, and local blood flow. Although researchers have not reached consensus regarding ideal tissue temperature after injury, Merrick et al 9 suggested that, in the absence of definitive data, better treatment outcomes may result from greater and faster cooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research [1][2][3][4][5][6] has shown that decreasing tissue temperature decreases pain, edema, nerve conduction, cellular metabolism, and local blood flow. Although researchers have not reached consensus regarding ideal tissue temperature after injury, Merrick et al 9 suggested that, in the absence of definitive data, better treatment outcomes may result from greater and faster cooling.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Ice is believed to help control pain by inducing local anesthesia around the treatment area. 3 Investigators have also shown that it decreases edema, 4 nerve conduction velocities, 5 cellular metabolism, 6 and local blood flow. 2 Researchers have studied the thermal effects of many methods of cold application by specifically looking at cutaneous and intramuscular tissue temperature change, [7][8][9][10][11][12][13][14][15][16] the relationship between temperature change and the depth of the targeted tissue, 7 and the type of cold application used.…”
mentioning
confidence: 99%
“…(27) In addition, early use of cryotherapy hastens regeneration and has been associated with significantly smaller haematomas, less inflammation and less tissue necrosis. (1,29) Educating athletes on the importance of early medical consultation following injury and improving medical accessibility (e.g. having readily available onsite medical patterns of movements after injury.…”
Section: International Association Of Athletics Federations Worldmentioning
confidence: 99%
“…Some studies have suggested that cryotherapy in acute injuries has beneficial effects, due to metabolism reduction than to circulatory changes (Hocutt 1982;Knight 1985;Schaser et al 2007). Previous works have shown that three intermittent sessions of cryotherapy, associated to muscle compression and applied immediately after primary muscle injury, were effective to reduce the area of secondary injury.…”
Section: Effect Of Cryolesion In the Enzymatic Activity Of Injured Ratsmentioning
confidence: 99%